A Proverb is a Product of Folk Wisdom (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The term proverb is derived from the Arabic word "qavlun" (to say, to speak), and in the Uzbek language it has become the term of one of the aphoristic genres, which is an example of folk wisdom, and is a well-said word, sentence or phrase. means nos. It can be seen that there is a direct semantic connection between the term genre and its poetic nature.